2016
DOI: 10.1016/j.bpj.2016.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Nitric Oxide Production by Endothelial Cells

Abstract: We present a biochemical model of the wall shear stress-induced activation of endothelial nitric oxide synthase (eNOS) in an endothelial cell. The model includes three key mechanotransducers: mechanosensing ion channels, integrins, and G protein-coupled receptors. The reaction cascade consists of two interconnected parts. The first is rapid activation of calcium, which results in formation of calcium-calmodulin complexes, followed by recruitment of eNOS from caveolae. The second is phosphorylation of eNOS by p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 77 publications
1
84
0
1
Order By: Relevance
“…An earlier study showed shear stress may activate Kir channels in a cell-attached mode though the channels in the pipette are not exposed to shear directly, suggesting that shear stress can activate these channels indirectly (Jacobs et al 1995). Possible upstream mechanosensors include but are not limited to integrins, glycocalyx, other ion channels, and G proteins (Ando & Yamamoto, 2009;Sriram et al 2016). Mechanosensitive ion channels, specifically those permeable to Ca 2+ , are believed to be a major source of entry for Ca 2+ into ECs upon exposure to shear stress (Wiesner et al 1997); however, any existing link between mechanosensitive Ca 2+ channel activation and subsequent Kir channel activation has yet to be investigated.…”
Section: Role Of Endothelial Kir21 In Flow-induced Vasodilatationmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study showed shear stress may activate Kir channels in a cell-attached mode though the channels in the pipette are not exposed to shear directly, suggesting that shear stress can activate these channels indirectly (Jacobs et al 1995). Possible upstream mechanosensors include but are not limited to integrins, glycocalyx, other ion channels, and G proteins (Ando & Yamamoto, 2009;Sriram et al 2016). Mechanosensitive ion channels, specifically those permeable to Ca 2+ , are believed to be a major source of entry for Ca 2+ into ECs upon exposure to shear stress (Wiesner et al 1997); however, any existing link between mechanosensitive Ca 2+ channel activation and subsequent Kir channel activation has yet to be investigated.…”
Section: Role Of Endothelial Kir21 In Flow-induced Vasodilatationmentioning
confidence: 99%
“…Mechanosensitive ion channels, specifically those permeable to Ca 2+ , are believed to be a major source of entry for Ca 2+ into ECs upon exposure to shear stress (Wiesner et al 1997); however, any existing link between mechanosensitive Ca 2+ channel activation and subsequent Kir channel activation has yet to be investigated. Shear also activates endothelial GPCRs and integrins that converge onto PIP 2 to promote IP 3 and PIP 3 formation, respectively (Chachisvilis et al 2006;Loufrani et al 2008;Sriram et al 2016), but a decrease in PIP 2 availability would be expected to deactivate rather than activate Kir channels. Another open question is whether an increase in Kir current is the result of an increase in the open probability of the channels, activation of previously dormant channels or insertion of new channels into the plasma membrane.…”
Section: Role Of Endothelial Kir21 In Flow-induced Vasodilatationmentioning
confidence: 99%
“…However, it remains unknown if increased shear stress, in the absence of muscle contraction, augments the vasodilator actions of insulin. Given that both shear stress and insulin activate eNOS through PI3K signalling pathways (Eringa et al 2002(Eringa et al , 2007Kim et al 2006;Sriram et al 2016), it is plausible that shear stress renders the vasculature more insulin-responsive. To test this hypothesis, complementary experiments were conducted using (i) cultured endothelial cells, (ii) isolated and pressurized skeletal muscle arterioles from swine, and (iii) humans.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of NO-np treatment was associated with a reversal of downregulated Akt/eNOS activities, and reversal of upregulated ROCK activity, in the SCD mouse bladder. We propose that increased local NO by NO-np treatment resulted in enhanced blood flow and shear forces on the urothelium, activated Akt/eNOS (Ser-1177) phosphorylation cascade, and promoted NO release and relaxation of the bladder (Dimmeler S et al, 1999;Sriram K et al, 2016;Hurt KJ et al, 2002). Increased NO may further downregulate the contractile ROCK pathway activity in the bladder, further improving bladder relaxation (Fig.…”
Section: Discussionmentioning
confidence: 93%